1993
DOI: 10.1111/j.1600-0447.1993.tb03455.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinicians’ information habits, patients’ knowledge of diagnoses and etiological concepts in four different clinical samples

Abstract: A total of 230 psychiatric inpatients and their physicians in charge took part in semistandardized interviews. Patients suffering from schizophrenia received information less frequently and less comprehensively than other patients. The label of schizophrenia was often paraphrased or not communicated at all; patients knew their diagnosis less exactly than other subgroups. Asked to indicate the most important cause of their disorder, neurotics tended to name their living conditions (60%), and addicts preferred t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
13

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 16 publications
1
21
0
13
Order By: Relevance
“…As diagnosis can be a challenging time for individuals (Cleary et al 2010a), their families (Greenwood et al 2000) and clinicians (Cleary et al 2010b) calls have been made to improve clinician competencies and confidence when initially discussing a diagnosis by providing training (Cleary et al 2010b;Gerrity et al 1999;Jha et al 2001;Luderer and Bocker 1993;Milton and Mullan in press;Scardovi et al 2003;Shergill et al 1998;Wong et al 2007) and developing protocols (Cleary et al 2009;Milton and Mullan in press). To address this need, a step-wise model of breaking news borrowed from oncology has been advocated [SPIKES protocol;See (Baile et al 2000;Cleary et al 2010a) and Table 2], and a model specifically tailored to discussing a schizophrenia diagnosis has been developed [See (Levin et al 2011) and Table 2].…”
Section: Introductionmentioning
confidence: 97%
“…As diagnosis can be a challenging time for individuals (Cleary et al 2010a), their families (Greenwood et al 2000) and clinicians (Cleary et al 2010b) calls have been made to improve clinician competencies and confidence when initially discussing a diagnosis by providing training (Cleary et al 2010b;Gerrity et al 1999;Jha et al 2001;Luderer and Bocker 1993;Milton and Mullan in press;Scardovi et al 2003;Shergill et al 1998;Wong et al 2007) and developing protocols (Cleary et al 2009;Milton and Mullan in press). To address this need, a step-wise model of breaking news borrowed from oncology has been advocated [SPIKES protocol;See (Baile et al 2000;Cleary et al 2010a) and Table 2], and a model specifically tailored to discussing a schizophrenia diagnosis has been developed [See (Levin et al 2011) and Table 2].…”
Section: Introductionmentioning
confidence: 97%
“…As with multiple sclerosis and other neurological illnesses, many patients with schizophrenia deny that they are ill. Only about one quarter of such patients accept that they have an illness, 21 which makes delivering a diagnosis problematic. This is why many clinicians are more comfortable talking to family members than to the patient.…”
Section: Introductionmentioning
confidence: 99%
“…Multifocal ( Schizophrenia was less frequently disclosed in service-user surveys (Luderer & Bocker, 1993); with 45% not receiving any information compared to an average of 20% for other diagnoses. This was also the case in psychiatrist surveys (Clafferty et al, 2001;Gantt & Green, 1985;Green & Gantt, 1987;Luderer & Bocker, 1993;McDonald-Scott et al, 1992;Shergill et al, 1998), except when episodes were recurrent (Clafferty et al, 2001).…”
Section: Factors Influencing Diagnostic Discussionmentioning
confidence: 96%
“…Rates of service-users receiving or having knowledge of their diagnosis were collected in nine (L-IV) studies (Cleary et al, 2010a;Ganesan et al, 2011;Luderer & Bocker, 1993;Magliano et al, 2008;Marzanski et al, 2002;Seedat et al, 2002;Shergill et al, 1998;Thornicroft et al, 2009;Trump & Hugo, 2006). Studies conducted prior to the past decade reported low rates of diagnostic discussion for both schizophrenia diagnoses and general MHD (30%-65%).…”
Section: Rates Of Diagnostic Discussionmentioning
confidence: 99%